59 Should The 'Normal' And 'Ideal' Nipple Position in A Male Influence the Surgeon When Planning Severe Gynaecomastia Correction?. (4th May 2021) - Tan, P; Dhaliwal, K; Khanna, A
Abstract: Background: The ideal nipple position of the male chest following gynecomastia surgery is well documented however with increased development of the chest muscles, the NAC placement can change, leading to the medial displacement of the nipple giving a poor aesthetic outcome. Therefore, we feel these measurements need to be applied to the patients build and take into consideration the patient's future fitness goals. Method: We have analysed photographs of 3 groups of men: super- athletes, athletes and severe gynaecomastia. We assessed the proportions of the chest in relation to the NAC and the degree of ptosis. Results: There is wide variation in the position of the nipple to the chest wall between each group with minor variation within each group. Based on this research we believe that surgeons should be circumspect when considering breast reduction with a Wise pattern in patients with severe gynaecomastia. In patient with increased development of the pectoralis major muscles, the NAC placement can change, leading to medial displacement of the nipple and ptosis and poor aesthetic result. Conclusions: We suggest a two-stage procedure, carried out on two separate occasions wound be more ideal than a single stage as this allows better long-term better positioning of the nipple.